Developing Pedagogical Strategies for Prenatal Nutrition as a Preventive Measure Against Down Syndrome - Sinaga, Agnes; Ramanda, Peni (International Journal of Pedagogy, 2025)
Having a healthy child, both physically and mentally, who grows and develops well is the hope of every parent. However, the birth of children with developmental disabilities, such as Down syndrome, remains a concern that must be addressed, particularly through preventive efforts. Down syndrome is a genetic disorder associated with intellectual disability, often linked to both genetic and environmental factors, including inadequate maternal nutrition during pregnancy. This study aims to develop pedagogical strategies for educating pregnant women on the importance of prenatal nutrition as a preventive measure against Down syndrome. Using a field study method, data were collected through observations and interviews to explore the understanding and practices of maternal nutrition among pregnant women. The findings indicate that adequate nutritional intake during pregnancy contributes significantly to reducing the risk of developmental disorders, including Down syndrome, beyond hereditary factors. The implication of this study highlights the importance of structured and accessible pedagogical interventions to raise awareness and promote responsible nutritional practices during pregnancy. It is hoped that the results can serve as a foundation for future educational programs that empower mothers to make informed decisions for the well-being of their unborn children.